O The Influence Of The Work Environment On Employee Performance At Pt Toba Surimi Industries Plant I - Puspita Fitriansyah (Citakonsultindo, 2023)
One of the most important assets owned by a company is human resources because they have an influence on the company's survival. Employees in a company need to be provided with a comfortable workplace in order to produce optimal performance. The work environment is an important thing for companies to pay attention to and is one of the factors determining employee performance. The aim of this research is to find out how the work environment, employee performance and the influence of the work environment on employee performance at PT Toba Surimi Industries Plant I. This research was conducted by distributing questionnaires to 116 employees at PT Toba Surimi Industries Plant I. Based on the research that has been carried out, an equation was obtained regression Y=40,404+0.438X. The results of the research state that the work environment and employee performance at PT Toba Surimi Industries Plant I have a moderate positive relationship with a value of 0.438 and the work environment influences employee performance.